Independent and Learning Outcome in Online Learning - Khairul Anwar; Ali Marzuki Zebua (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to determine and analyze the effect of Independence on Learning Outcomes in online learning during the Covid 19 pandemic. This research applies explanatory survey method. The object of this research is the State Islamic Institute (IAIN Kerinci). The sample in this study was all 6th semester Islamic Education Management Students, totaling 65 people. The results of the study showed that there was a correlation between independent learning and learning outcomes during the COVID-19 pandemic with a moderate correlation. As for the level analysis for the variable of learning independence during the Covid 19 pandemic with the dimension of self-confidence being at a moderate level, the dimension of self-learning being at a moderate level, the dimension of mastering expertise in the field is at a moderate level, the dimension of respecting time is at a high level, and the dimension of respecting time is at a high level. responsibility is at the moderate level. Meanwhile, the level analysis for the learning outcome variables on the affective dimension is at a high level, the psychomotor dimension is at a moderate level and cognitive is also at a moderate level.